The Employment of Standard Addition Method for the UV Spectrophotometric Assay of Diclofenac Alkaline Salts in Variant Pharmaceutical Dosage Forms - Zaid Mahdi Jaber Al-Obaidi (Journal of Global Pharma Technology, 2018)
Objective: The standard addition method is widely utilised in the drug analysis protocols. The objective of this study is to perform a fast, easy, economy, and reliable method for the quantitation of diclofenac in different pharmaceutical dosage forms utilizing standard addition method with the employment of UV-Vis spectrophotometric technique. Methods: Four different dosage forms of diclofenac were selected to be analysed. These include: tablets, ampules, Emulgel, and powders for oral use. After preparing the samples with well-conducted procedures, the prepared samples were inoculated with predetermined spikes of the standards. Consequently, these prepared samples were analysed employing UV-Vis techniques. Results: As a result, the plotted standard curves for Cataflam, Voltaren Emulgel, Voltafast sachets, and Voltaren ampule showed good linearity with regression coefficients of 0.9984, 0.9988, 0.9981, 0.9992, and 0.9996 for respectively. The Limit of detection (LOD = 3SD) and Limit of quantification (LOQ = 10SD) were calculated for each dosage form. With the aid of the straight line equations, sample concentration was estimated for both techniques. The percent amount was found to be 99.04%, 105.5%, 98.64%, and 99.32% in respective order to the mentioned four diclofenac salts. Conclusion: The authors conclude that the standard addition method utilised in UV-Vis was as accurate, precise, fast, and economy, thus, can be used in routine laboratory drug-analyses.Keywords: Standard addition, Diclofenac sodium, Diclofenac potassium, Diclofenac diethylamine, Voltaren, Emulgel, Voltafast, Cataflam, UV-Vis, Diclofenac quantification.